UNIFIKASI REGULASI KEADILAN RESTORATIF MELALUI SISTEM PERADILAN PIDANA INDONESIA - Jamaludin, Ahmad; Saputra, Dandi Ditia (Universitas Muhammadiyah Ponorogo, 2023)
Internationally, restorative justice resonates most in and out of the criminal justice system. The justice system's slow pace has led to a backlog of cases at law enforcement agencies and prison overcrowding in Indonesia. This study seeks to understand Indonesia's restorative justice practices at all law enforcement levels. This study used normative juridical research, which included comparative, conceptual, and statutory approaches. Based on their binding force, primary, secondary, and tertiary legal materials are used in this research. The data was analyzed descriptively and qualitatively. The results showed that Indonesia's restorative justice rules are based on the Circular Letter of the Chief of the Indonesian National Police, the Regulation of the Chief, and the Decree of the Director General of the General Justice Office of the Supreme Court, which differ in the scope of criminal offenses that can be subject to restorative justice. This could lead to inconsistencies in its application. However, the mechanism for implementing a restorative justice-based criminal justice system should be unified and partially codified in legislation, such as government regulations strengthened by several provisions in the draft Criminal Procedure Code.